A Analisis Pengaruh Inflasi,Suku Bunga, Dan Kurs Terhadap Pertumbuhan Ekonomi Di Indonesia: Pengaruh Inflasi,Suku Bunga, Dan Kurs Terhadap Pertumbuhan Ekonomi Di Indonesia - Jaswandi, Amir Khairul Haq; Fadlurohman, Isnain Farhan (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of inflation, interest rates, and exchange rates on economic growth in Indonesia. Economic growth is a key indicator in evaluating the performance of a country's economy, making it crucial to understand the factors that impact it, which has significant implications for economic policy. The data used in this research is secondary data in the form of time series data from the year 2000 to 2023, obtained from official sources such as the Central Bureau of Statistics (BPS) and Bank Indonesia (BI). The analytical method employed is multiple regression, which allows for identifying the relationship between independent variables inflation, interest rates, and exchange rates and the dependent variable, which is economic growth measured through Gross Domestic Product (GDP). The results of the study indicate that inflation, interest rates, and exchange rates have significant effects on economic growth. Inflation was found to have the most dominant negative impact, showing that high inflation rates can hinder economic growth by reducing purchasing power and disrupting investment